2005
DOI: 10.1002/macp.200590034
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Chem. Phys. 17/2005

Abstract: Cover: Gas-phase assisted surface polymerization (GASP) of methyl methacrylate (MMA) with a simple initiating system, Fe(0)/abromophenylacetate (MBPA), produced high molecular weight PMMA on Fe(0)-metal surfaces, suggesting a physically controlled propagation process on the surfaces. Further details can be found in the Full Paper by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Bulk polymerization of MMA with simple initiator system: Fe(0)/organic halides In a previous report, 16 it was found that a simple initiator system Fe(0)/methyl a-bromophenylacetate (MBP) was able to initiate the radical polymerization of MMA on iron powder surfaces in a gas phase, suggesting a physically controlled polymerization behavior; that is, it was shown that the molecular weight of the obtained polymer increased with increase in its yield. However, the number-average molecular weight (M n ) of the obtained polymer was lower than 7400 even after 24 h at 608C, suggesting a slow propagation process.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Bulk polymerization of MMA with simple initiator system: Fe(0)/organic halides In a previous report, 16 it was found that a simple initiator system Fe(0)/methyl a-bromophenylacetate (MBP) was able to initiate the radical polymerization of MMA on iron powder surfaces in a gas phase, suggesting a physically controlled polymerization behavior; that is, it was shown that the molecular weight of the obtained polymer increased with increase in its yield. However, the number-average molecular weight (M n ) of the obtained polymer was lower than 7400 even after 24 h at 608C, suggesting a slow propagation process.…”
Section: Resultsmentioning
confidence: 97%
“…Results are listed in Table II. During the GASP of MMA, the surface color of Fe(0) powder changed from gray to dark red, which indicated the formation of oxidized species, Fe(II) and/or Fe(III) chlorides on the Fe(0) surface as previously reported when using the Fe(0)/MBP system. 16 A large amount of deposit was found on the Fe(0) powder surface with a simple system Fe(0)/TsCl without ligand (run 2-1). Interestingly, this system gave a high molecular weight polymer of 36,000 M n , showing a high initiator efficiency of 0.0221 in comparison with the result in the liquid phase (Table I).…”
Section: Gasp Of Mma With Fe-compound/tscl Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] One of the most widely employed and efficient living radical polymerizations is the one based on a metal catalyst that generates the growing radical species from the carbon-halogen polymer terminal via the reversible redox reaction of the metal center. The various effective central metals, such as Ru(II), 8 Cu(I), [9][10][11] Ni(II), 12,13 Fe(II), [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and so forth, give one electron upon the formation of the radical species from the dormant carbon-halogen covalent bond and thus should be basically in a low oxidation state.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Alternatively, iron(III) halides were employed in conjunction with similar ligands in the presence of a radical initiator like 2,2 0 -azobisisobutyronitrile (AIBN), in which Fe(III) was reduced to Fe(II) via the reaction with the initiating radical species (RÁ) along with the formation of an alkyl halide (RAX).…”
Section: Introductionmentioning
confidence: 99%